National Kidney Foundation's primer on kidney diseases - Gilbert, Scott; Weiner, Daniel (Elsevier, 2023)
The thoroughly revised 8th Edition of this authoritative, practical reference covers every relevant topic in the field, making it an excellent resource for residency, fellowship, clinical practice, and board review. Covers every relevant topic in nephrology―from anatomy, physiology, and pathophysiology to diagnosis and management of kidney disease, to fluid and electrolyte disorders, hypertension, dialysis, and renal transplantation. Offers new guidance for management of COVID-19 in the Viral Nephropathies chapter. Enhanced eBook allows you to access all of the text, figures, and references from the book on a variety of devices.